Marriage, Divorce, and Distress in Northeast Brazil : Black Women's Perspectives on Love, Respect, and Kinship - Medeiros, Melanie A. (Book collections on Project MUSE., 2018)
Using an intersectional approach, Marriage, Divorce, and Distress in Northeast Brazil explores rural, working-class, black Brazilian women's perceptions and experiences of courtship, marriage and divorce. In this book, women's narratives of marriage dissolution demonstrate the ways in which changing gender roles and marriage expectations associated with modernization and globalization influence the intimate lives and the health and well being of women in Northeast Brazil. Melanie A. Medeiros explores the women's rich stories of desire, love, respect, suffering, strength, and transformation.